Armored heart as an image of constrictive pericarditis - a review of the literature - Wojciech Wokurka; Agata Węgrzyniak; Dominik Drobek; Aleksandra Winiarz; Paula Szlendak; Katarzyna Toś; Kacper Wojtala; Michał Turek; Katarzyna Wąsala; Sylwia Grosman (Kazimierz Wielki University, 2023)
Introduction: Pericarditis is diagnosed among 5% patients hospitalized due to chest pain. It is included in pericardial syndromes together with constrictive pericarditis, pericardial effusion and cardiac tamponade. There are many documented etiological factors leading to pericarditis, most commonly divided into infectious and non-infectious ones. The disease typically presents with chest pain, ECG changes, pericardial rub and pericardial effusion. The diagnosis is made with the results of parameters found in patients' blood and imaging tests. Treatment is usually based on pharmacological therapy, although in some cases the pericardial surgery is necessary. One of the characteristic changes in imaging diagnostics in patients with pericarditis is thickening of pericardial layers, the so-called armored heart. Aim of the study: The aim of the study was to find clear diagnostic criteria for armored heart as a unique type of constrictive pericarditis. Materials and methods: Articles available in the databases of medical publications: PubMed, Google Scholar, SCOPUS were analysed using the search phrase: armored heart* AND (pericarditis OR acute pericarditis). Results: The search phrase was included in 18 records. After the initial verification, repetitive, unavailable and foreign papers were rejected. Finally, 3 manuscripts were included in further analyses. No clear criteria were found to classify constrictive pericarditis as an armored heart. Conclusions: Armored heart is a 'subtype' of constrictive pericarditis. It seems that this term is used subjectively, based on imaging studies.